To solve this, you combine like terms. So, put the two Bs together, and put the two As together, and you have your answer!
(18b - 9b) + (5a + 2a)
9b + 7a
2007-01-09 08:09:37
·
answer #1
·
answered by Anonymous
·
1⤊
0⤋
Reorganize the terms in order to more effectively see the relationships.
18b - 9b + 5a + 2a
Combine like terms
9b + 7a
2007-01-09 08:06:59
·
answer #2
·
answered by smawtadanyew 2
·
1⤊
0⤋
First: combine "like" terms ...
18b - 9b + 5a + 2a
9b + 7a
2007-01-09 10:39:01
·
answer #3
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
All I can do is: Combine the terms to get 9b = -3a. Then, divide by 3: 3b = -a. So if a = 1, b = -1/3
a = 2, b = -2/3
a = -1/3, b= 1/9...etc
2007-01-09 08:14:29
·
answer #4
·
answered by Richard S 6
·
0⤊
1⤋
5a + 2a = -18b + 9b
7a = -9b
2007-01-09 08:08:52
·
answer #5
·
answered by Anonymous
·
0⤊
1⤋
7a+9b
2007-01-09 08:06:21
·
answer #6
·
answered by ccjcjl 2
·
1⤊
0⤋
9b+7a
2007-01-09 08:05:16
·
answer #7
·
answered by bequalming 5
·
1⤊
0⤋
think of it as:
18 apples + 5 pears - 9 apples + 2 pears = 9 apples + 7 pears
2007-01-09 08:04:55
·
answer #8
·
answered by krumenager 3
·
1⤊
0⤋